MATH SOLVE

2 months ago

Q:
# For the following system, use the second equation to make a substitution for y in the first equation.3x + y = 1y + 4 = 5xWhat is the resulting equation?3x + 5x - 4 = 13x + 4 - 5x = 13x + 5x + 4 = 1

Accepted Solution

A:

Answer:Option A: Β 3x + 5x - 4 = 1Step-by-step explanation:Given equations:3x + y = 1 Β ------------ eq1y + 4 = 5x ---------- eq2eq2 can also be written as:y = 5x - 4 ----------- eq3By substituting value of y from eq 3 into eq1, the resulting equation will be:3x + 5x - 4 = 1i hope it will help you!